MORPHOLOGICAL, PHYSIOLOGICAL AND BIOCHEMICAL STUDY OF In vivo AND In vitro RAISED Centella asiatica (L.) Urban - KANCHAN JOSHI; PREETI CHATURVEDI (International Journal of Pharma and Bio Sciences, 2013)
Centella asiatica (L.) Urban is commonly used for curative rationale and food relevance. In the present study, certain morphological, physiological and biochemical parameters of in vivo and in vitro raised plants were compared. In vitro grown plant exhibited high level of chlorophyll (1.360 g/ fresh wt.), increased leaf area (2.5-3.5× 3.9-6.6 cm), low amount of phytic acid (2 mg/100mg), low ascorbic acid (10.95 mg/100g) and low SOD activity (428.52 unit/g) whereas in vivo grown plant exhibited reduced amount of chlorophyll (0.930 mg/g fresh wt.),decreased leaf area (1.8-2.7× 3.6-4.3 cm), increased level of phytic acid (3 mg/100g ), ascorbic acid (12.44 mg/100g) and high SOD activity (491.22 unit/g). Study of these parameters restrengthens the potential of plant as nutraceutical for its food value as well as medicinal applications.